Can coase govern the Green Bay Packers?. Issue 3 (9th March 2015) - Chen, Jia-Yuh; Khadka, Manish
Abstract : Purpose: – The agency problem inherent in governing public corporations predicts a management not acting in shareholders' best interest. The purpose of this paper is to use the Green Bay Packers' unique ownership structure as a case study to show that a disperse shareholder base does not necessarily lead to failures in corporate governance. Design/methodology/approach: – The Packers have been run by a great management team since 1992. The authors argue that the new management has become the de facto owners of the Packers organization and dealt away the agency costs as a result. This argument is in line with the Coase Theorem. Findings: – The ownership of the Packers is a property. As would be argued with the Coase Theorem, if the property right is well defined, who controls the property, under certain circumstances, is irrelevant in regard of maximizing ownership value. Research limitations/implications: – With only one sample point, the authors, however, cannot rule out the randomness of the Packers' stellar performance and also the possibility that the new management acts in the best interest of Packers shareholders because they have well-designed employment contracts. Originality/value: – Nevertheless, the findings offer a new perspective to the corporate governance literature.